1992
DOI: 10.1002/hup.470070302
|View full text |Cite
|
Sign up to set email alerts
|

PET analysis of central [11 C]raclopride binding in healthy young adults and schizophrenic patients—reliability and age effects

Abstract: Central D2-dopamine receptor occupancy determined by positron emission tomography (PET) during neuroleptic drug treatment may be a useful measure for optimal dose finding in schizophrenic patients. The clinical benefit is dependent on the reliability of such determinations. The ratio of radioactivity in the striatum to that of the cerebellum 1s widely used for calculation of D2-receptor occupancy and as an index of D2-dopamine receptor density. To test the reliability of such ratios a test-retest analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
19
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(24 citation statements)
references
References 30 publications
5
19
0
Order By: Relevance
“…= 0.51, k4 = 0.14) with k31k4 = 3.68, which is very close to the values reported here (Brnax'IKd/)' They could not, however, assess reproducibility since their second studies were at low specific activity. Reproducibility of raclopride binding as determined by the ratio of integrated radioactivities (from 21 to 33 min) for putamen to CB has been reported by Nordstrom et al (1992). The mean of the ratio of the integrated radioactivities of putamen to CB from study 2 (retest) to study 1 (test) was found to be 1.01 with an SD of 0.07, which is similar to the repro ducibility of DV ratios reported by Volkow et al (1993a) and to Brnax'IKd' values reported here.…”
Section: Discussionmentioning
confidence: 94%
“…= 0.51, k4 = 0.14) with k31k4 = 3.68, which is very close to the values reported here (Brnax'IKd/)' They could not, however, assess reproducibility since their second studies were at low specific activity. Reproducibility of raclopride binding as determined by the ratio of integrated radioactivities (from 21 to 33 min) for putamen to CB has been reported by Nordstrom et al (1992). The mean of the ratio of the integrated radioactivities of putamen to CB from study 2 (retest) to study 1 (test) was found to be 1.01 with an SD of 0.07, which is similar to the repro ducibility of DV ratios reported by Volkow et al (1993a) and to Brnax'IKd' values reported here.…”
Section: Discussionmentioning
confidence: 94%
“…However, it is reasonable to assume that the reliability is comparable to the high reliability (5.8%, n ϭ 6) observed in humans . The monkey brain is smaller but the 3D-PET-system used in the present study has higher resolution, 3.7 mm FWHM (Wienhard et al, 1994), than the old system, Scanditronix PC-384-7B, 8.5 mm FWHM (Litton et al, 1984), used in the human study by Nordström et al (1992). Furthermore, the assumption of a similarly low test-retest variability in the determination of B max in humans and intact monkeys is indirectly supported by a recent PET study performed in our center (Ginovart et al, 1997).…”
Section: Discussionmentioning
confidence: 96%
“…41,42 To achieve comparable results for the two different PET systems, B/Fratios obtained with the Scanditronix 384-7B were multiplied by 1.14 according to a previously published comparative study. 32 To avoid a possible influence from dopamine D3 receptors in the nucleus accumbens the ventral striatum was not included in the region of interest.…”
Section: Positron Emission Tomographymentioning
confidence: 99%